Pastor victory Abelsen and the three hunter deacons (teachers from the settlements at Scoresby ... : Pastor Sejer Abelsen og de tre fangerkateketere (lærere fra bopladserne ved Scoresby Sund), Grønland 1930 - Petersen, Sofie (University of Southern California Digital Library (USC.DL), 2015)
Pastor victory Abelsen and the three hunter deacons (teachers from the settlements at Scoresby Sund), Greenland 1930